UNDERSTANDING YOUTH MENTAL HEALTH: A CRITICAL EXAMINATION OF PERSONALITY DISORDERS IN JENNIFER NIVEN'S ALL THE BRIGHT PLACES - Ali, Muhammad Ilham; Katili, Yayu Anggrani H.; Simanjuntak, Rutmintauli (Dialectical Literature and Educational Journal, 2024)
This study examines the manifestation of personality disorders through the character of Theodore Finch in the film adaptation of "All the Bright Places." The research specifically analyzes how Finch's personality disorder affects his behavior, relationships, and ultimate fate within the narrative. Employing a descriptive qualitative method, the study collects data through careful examination of selected scenes that demonstrate Finch's personality disorder symptoms. The theoretical framework utilizes Freud's structural model of personality, focusing on the id, ego, and superego as fundamental components that shape human behavior and decision-making processes. The analysis reveals that Finch's personality is significantly influenced by the dynamic interplay between these three psychic structures. The findings demonstrate how his impulsive actions are predominantly driven by the id's pleasure principle, while his ego attempts to mediate between his internal desires and external reality. Additionally, the study shows how his superego's moral constraints create internal conflicts that contribute to his psychological struggles. Through scene-by-scene analysis, this research provides insights into the complex representation of mental health in contemporary cinema and contributes to the broader understanding of how personality disorders are portrayed in modern media. The study's findings offer valuable perspectives for both film analysis and psychological character studies